2021
DOI: 10.1186/s13229-021-00459-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of intranasal oxytocin in Phelan-McDermid syndrome

Abstract: Background Phelan-McDermid syndrome (PMS) is a rare neurodevelopmental disorder caused by haploinsufficiency of the SHANK3 gene and characterized by global developmental delays, deficits in speech and motor function, and autism spectrum disorder (ASD). Monogenic causes of ASD such as PMS are well suited to investigations with novel therapeutics, as interventions can be targeted based on established genetic etiology. While preclinical studies have demonstrated that the neuropeptide oxytocin can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…A small study of 18 children with SHANK3 haplotype insufficiency (Phelan-McDermid syndrome) has also been published using intranasal oxytocin with a p-value approaching, but not quite reaching, the threshold for significance at 12 weeks (p = 0.055). Changes on the Aberrant Behavior Checklist-Social Withdrawal (ABC-SW) was the endpoint measured in this study [39]. All of the above findings, along with the published studies of intranasal oxytocin being used and having a demonstrated benefit in children with ASD [40], made oxytocin qualify to be listed as a potential intervention for SHANK3 for the genomic CDS described.…”
Section: Address Downstream Pathways and Effectsmentioning
confidence: 60%
“…A small study of 18 children with SHANK3 haplotype insufficiency (Phelan-McDermid syndrome) has also been published using intranasal oxytocin with a p-value approaching, but not quite reaching, the threshold for significance at 12 weeks (p = 0.055). Changes on the Aberrant Behavior Checklist-Social Withdrawal (ABC-SW) was the endpoint measured in this study [39]. All of the above findings, along with the published studies of intranasal oxytocin being used and having a demonstrated benefit in children with ASD [40], made oxytocin qualify to be listed as a potential intervention for SHANK3 for the genomic CDS described.…”
Section: Address Downstream Pathways and Effectsmentioning
confidence: 60%
“…The results of earlier continual OT trials in children with ASD have been equivocal: some with beneficial outcomes (Parker et al, 2017; Yatawara et al, 2016), while others without significant effect (Fastman et al, 2021; Guastella et al, 2015; Sikich et al, 2021). While it is difficult to pinpoint the different factors contributing to variability in study results, several key differences in adopted dosing schema, trial design, and participant demographics have been put forward as important moderators.…”
Section: Discussionmentioning
confidence: 99%
“…Two initial trials reported a consistent pattern of results, indicating improvements in the social domain (parent-reported social responsiveness) after five weeks of intranasal OT treatment in 3-to-6-year-old children (n = 31; cross-over; Yatawara et al, 2016) and after four weeks of treatment in 6-to-12-year-old children with ASD (14 OT / 18 placebo; Parker et al, 2017). No significant improvements on core autism symptoms were demonstrated, however, after an eight-week OT treatment in adolescent boys with ASD (26 OT / 24 placebo; 12-18 years; Guastella et al, 2015) or in a preliminary 12-week administration trial encompassing a broad age range of 5-to-17-year-old children (8 OT / 10 placebo) with Phelan-McDermid syndrome (characterized by ASD symptoms; Fastman et al, 2021). Also, in a recent confirmatory trial including 3-to-17-year-old children with ASD (139 OT / 138 placebo) and an age-adjusted dosing scheme ranging from 8-80 IU, no improvements on outcomes of social functioning were evident after 24 weeks of OT treatment (Sikich et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, individuals with high ABC-SW scores display reduced levels of expression for these genes. Given the interest in the ABC-SW as a clinical outcome assessment of treatment efficacy in clinical trials of PMS, 68 , 69 peripheral biomarkers that scale ABC-SW severity may serve as a valuable resource to monitor treatment responses and outcomes in PMS and other disorders that present with social withdrawal phenotypes. However, further follow-up of these genes and their dynamic expression profiles following administration of such therapeutic agents is warranted.…”
Section: Discussionmentioning
confidence: 99%